Studi Perbandingan Hasil Belajar IPS Terpadu dengan Menggunakan STAD dan PBL - Roma Rio Purba; Tedi Rusman; Nurdin Nurdin (FKIP Unila, 2018)
The purpose of this study was to determine the comparative study of integrated IPS learning outcomes using the Student Team Achievement Division (STAD) and Problem Based Learning (PBL) models by paying attention to the Learning Motivation of Grade VII Students of Gajah Mada Middle School in Bandar Lampung. This study uses a comparative research design with an experimental approach. The population in this study were all seventh grade students of Gajah Mada Junior High School Bandar Lampung and a sample of 60 respondents determined by clustur random sampling technique. Data collection was carried out using the method of filling out questionnaires and test techniques. Data collected through questionnaires is processed with the SPSS program. The results of the data analysis showed that there was a comparison of the integrated IPS learning outcomes using the Student Team Achievement Division (STAD) and Problem Based Learning (PBL) models by paying attention to the Learning Motivation of Grade VII Students of Gajah Mada Middle School in Bandar Lampung. Tujuan penelitian ini untuk mengetahui studi perbandingan hasil belajar ips terpadu dengan menggunakan model Student Team Achievement Division (STAD) dan Problem Based Learning (PBL) dengan Memperhatikan Motivasi Belajar pada Siswa Kelas VII SMP Gajah Mada Bandar Lampung. Penelitian ini menggunakan desain penelitian komparatif dengan pendekatan eksperimen. Populasi dalam penelitian ini yaitu seluruh siswa kelas VII SMP Gajah Mada Bandar Lampung dan sampel 60 responden yang ditentukan dengan teknik clustur random sampling. Pengumpulan data dilakukan dengan menggunakan metode pengisian kuesioner dan teknik tes. Data yang dikumpulkan melalui angket diolah dengan program SPSS. Hasil analisis data menunjukkan bahwa ada perbandingan hasil belajar ips terpadu menggunakan model Student Team Achievement Division (STAD) dan Problem Based Learning (PBL) dengan Memperhatikan Motivasi Belajar pada Siswa Kelas VII SMP Gajah Mada Bandar Lampung. Kata Kunci : hasil belajar, PBL, STAD